SISTEM INFORMASI PENGELOLAAN DATA INVENTARIS DAN BARANG HABIS PAKAI BERBASIS MICROSOFT ACCESS 2010 PADA SD NEGERI TANGKISAN KECAMATAN BAYAN PURWOREJO - Suhartini, Titik; Zahwa, Ainun (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2025)
SD Negeri Tangkisan is one of the government-owned educational institutions located in Krajan Hamlet, RT 02 / RW 01, Tangkisan Village, Bayan District, Purworejo Regency. The management of inventory data and consumables has been recorded using a computerized system but still using Microsoft Excel, this is less effective and efficient. Based on this description, the author conducted research using data collection techniques in the form of observation, interviews, documentation, and literature studies, with descriptive qualitative and quantitative data analysis techniques. The author designs an information system for managing inventory data and consumables using Microsoft Access 2010, this system is designed to facilitate the management of inventory data and consumables in adding, deleting, printing, creating reports, and searching data more effectively and efficiently. The results of the system implementation show an increase in the effectiveness and efficiency of managing inventory data and consumables at SD Negeri Tangkisan. Users can easily access this information system because this system is simpler and easier to use.